Innovation and Self-Employment - Tommaso Ciarli; Mattia Di Ubaldo; Maria Savona (Global Labor Organization (GLO), 2020)
The paper adds to the literature on innovation and employment by looking at the relationship between R&D investments and the rise of alternative work arrangements, particularly selfemployment (SE). A literature review on the determinants of the emergence of non-standard work, alternative work arrangements and self-employment if offered first. The contributions that have looked at SE in relation to innovation strategies is surprisingly limited. General trends of SE in Europe are considered. The empirical contribution is focused on the analysis of local labour markets in the UK (Travel-To-Work-Areas, TTWAs), where their initial concentration of routinized and non-routinized jobs is considered. The probability that an individual shifts from paid employment to either unemployment or self-employment over the period 2001-13, as linked to changes in R&D investments in the TTWA is empirically accounted for. Results show that overall R&D has negligible effects on the probability of workers to become self-employed. R&D increases the probability of moving from unemployment to paid employment, especially in routinized areas, and reduces the permeability between routinised and nonroutinised workers. Also, a non-negligible increase in the probability that a routinized worker becomes SE as a result of R&D increase is found in low routinised local labour markets, but not in highly routinised areas. The paper sheds new lights on the effect of R&D on employment and self-employment in areas with different degrees of routinization, and adds to the discussion on the more general raise of alternative work arrangements in Europe by disentangling the characteristics of self-employment as resulting from R&D investments.
Keywords: J6; O3; O32; 330; R&D; employment; unemployment; self-employment; routinized local labour markets